Factors influencing online shopping behaviors of Facebook users among undergraduate students in UUM, Sintok, Kedah - Fazira, Ahmad Tajudin (2015)
Online shopping in Malaysia is a new technology innovation since it has just begun to beating the Malaysia retailing sector with online shopping services. Online buying behavior process discusses about the products bought through online. The process of online buying behavior is kind of similar to traditional shopping behavior except there is no face to face transaction occurred. The aim of this study is to investigate the factors that influencing the online shopping behavior among students. This study is focus on undergraduate students in university Utara Malaysia, Sintok, Kedah who have the Facebook account. A total number of 250 students chosen as respondents but only 168 of them responded to the questionnaire. Statistical Package software for Social Science (SPSS) Version 22.0 was used to analyze the collected data. Reliability analysis, multiple regressions and correlation were applied to this study. The Pearson correlation analysis indicated that perceived risk is a negatively associated with actual online shopping behavior whereas attitude and experience have positive relationship with dependent variable. Furthermore, the multiple regression analysis revealed that all the independent variables have significant prediction on dependent variable. It is suggested for future research to look at the way to influence the attitudes of online buyers among student by investigate some other important factors that able to improve their buying behavior in the future